2015
DOI: 10.1016/j.molonc.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive sensitive detection of KRAS and BRAF mutation in circulating tumor cells of colorectal cancer patients

Abstract: Characterization of genetic alterations in tumor biopsies serves as useful biomarkers in prognosis and treatment management. Circulating tumor cells (CTCs) obtained non-invasively from peripheral blood could serve as a tumor proxy. Using a label-free CTC enrichment strategy that we have established, we aimed to develop sensitive assays for qualitative assessment of tumor genotype in patients. Blood consecutively obtained from 44 patients with local and advanced colorectal cancer and 18 healthy donors were enri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…These findings are in favor of characterizing CTCs with a molecular approach even if only part of the CTCs harbors the mutation of interest. In another recent study, the IBN microsieve size based filtration unit (Lim et al., 2012) was coupled to molecular KRAS mutation detection using HRM (High Resolution method) and ASPCR (Allele specific PCR) methodology (Mohamed Suhaimi et al., 2015). This study reported sensitivity for both technics estimated at 1.25%.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in favor of characterizing CTCs with a molecular approach even if only part of the CTCs harbors the mutation of interest. In another recent study, the IBN microsieve size based filtration unit (Lim et al., 2012) was coupled to molecular KRAS mutation detection using HRM (High Resolution method) and ASPCR (Allele specific PCR) methodology (Mohamed Suhaimi et al., 2015). This study reported sensitivity for both technics estimated at 1.25%.…”
Section: Discussionmentioning
confidence: 99%
“…The use of new sensitive new generation sequencing methods can also be an alternative option [36]. However, the best solution may arise from peripheral blood testing since circulating tumor cells and circulating tumor DNA are the reflection of the whole tumor [37,38]. These technologies provide another avenue to detect mutations, especially in patients with lymph nodes or distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this progress, there is substantial agreement that analysis should incorporate molecular profiling of CTCs, not just enumeration, in order to assess their metastatic potential and predict either tumor progression, detect relapse, or monitor response to specific therapies 35 . Prior studies have demonstrated the ability of a panel of markers to improve the overall prognostic impact, compared to individual targets 31 45 46 47 48 49 , and the ability of molecular profiling of CTCs from different tumor types, for gene expression as well as mutational status of key cancer-related genes (KRAS 36 , BRAF 37 , PI3KCA 38 39 , EGFR 40 , etc) to provide valuable insights into the biology and behavior of the primary tumor 41 42 43 44 . In the present study, clustering of GEFs together improved the prognostic accuracy of the individual family members.…”
Section: Discussionmentioning
confidence: 99%